2005
DOI: 10.1016/j.abb.2005.03.020
|View full text |Cite
|
Sign up to set email alerts
|

CYP35: Xenobiotically induced gene expression in the nematode Caenorhabditis elegans

Abstract: Abstract:Although over 80 cytochrome P450 (CYP) encoding genes have been identified in the genome of the nematode Caenorhabditis elegans very little is known about their involvement in biotransformation. This paper demonstrates a concentration dependent relationship of C. elegans CYP35A1, A2, A5, and C1 gene expression in response to four organic xenobiotics, namely atrazine, PCB52, fluoranthene, and lansoprazole. The toxicity of these xenobiotics was determined using a reproduction assay. CYP-specific messeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 48 publications
4
77
0
Order By: Relevance
“…The cyp-35-family is known to be inducible by xenobiotics (Menzel et al 2005a). The same is visible with several gst-genes, and one cdr-and ugt-gene each.…”
Section: Resultsmentioning
confidence: 99%
“…The cyp-35-family is known to be inducible by xenobiotics (Menzel et al 2005a). The same is visible with several gst-genes, and one cdr-and ugt-gene each.…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24][25][26] The cytochrome p450 monooxygenases responsible for production of the EETs and EpOMEs are present in the genome, though few have been characterized. [27][28][29] Finally, C. elegans contain arachidonic acid and linoleic acid, the precursors of these signaling molecules. [30,31] The genome of C. elegans contains five enzymes which display significant sequence similarity to the mammalian sEH.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an expansion in the CYP superfamily is present in insects and nematodes with 90 CYPs being predicted in Drosophila [4] and 83 in Caenorhabditis elegans [5]. Earlier studies have shown that some members of cellular metabolism gene families, particularly the CYPs, are highly inducible in C. elegans by a range of small organic molecules [6][7][8]. We have recently shown that members of the CYP family are also induced by thiabendazole [TBZ; 2-(4-thiazolyl)-1H-benzimidazole] in C. elegans and that the most inducible CYP with the highest expression and for the longest duration is regulated by nhr-176 [9].…”
Section: Introductionmentioning
confidence: 99%